2006
DOI: 10.1007/s10571-006-9069-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress Triggered Changes in Gene Expression in Adrenal Medulla: Transcriptional Responses to Acute and Chronic Stress

Abstract: 1. Stress elicits activation of several transcription factors involved in the regulation of catecholamine biosynthetic enzyme gene expression depending on its duration or repetition. However, the dynamic of the conversion of transient transcriptional activation with acute stress to sustained changes in transcription in response to repeated exposure to stress in adrenomedullary catecholaminergic systems is not clear. 2. Here, we analyzed changes in levels of phospho-CREB (P-CREB), phospho-ERK1/2 (P-ERK1/2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
1
33
1
Order By: Relevance
“…We have previously shown that both acute and repeated IMO leads to a very marked induction of Egr1 expression (Papanikolaou and Sabban 1999;Liu et al 2008). However, in contrast, phosphorylation of CREB in the adrenal medulla is only robustly increased with repeated exposure to IMO (Sabban et al 2006) and may be involved in the induction of CgA and CgB gene expression observed here. Enhanced phosphorylation of CREB is also involved in transactivation of the CgA gene (Cramer et al 2008).…”
Section: Discussioncontrasting
confidence: 59%
“…We have previously shown that both acute and repeated IMO leads to a very marked induction of Egr1 expression (Papanikolaou and Sabban 1999;Liu et al 2008). However, in contrast, phosphorylation of CREB in the adrenal medulla is only robustly increased with repeated exposure to IMO (Sabban et al 2006) and may be involved in the induction of CgA and CgB gene expression observed here. Enhanced phosphorylation of CREB is also involved in transactivation of the CgA gene (Cramer et al 2008).…”
Section: Discussioncontrasting
confidence: 59%
“…Alternatively, interaction between ZO-1 and Cx36/Cx43 may modify their trafficking and/or facilite their interactions with other proteins. As shown by qPCR experiments and reported for genes encoding catecholamine-synthesizing enzymes and related transcription factors (Baruchin et al, 1990;Sabban and Kvetnansky, 2001;Sabban et al, 2006), mechanisms taking place at the transcriptional level can also be involved. We show that in cold stressed rats, the Cx36 protein expression level faithfully parallels the Cx36 mRNA expression level, as opposed to Cx43, for which the mRNA expression level remains unchanged.…”
Section: Long-term Persistence Of Changes In Gap Junction-mediated Comentioning
confidence: 94%
“…Sabban et al (2004) extended these findings by reporting elevations in catecholamine biosynthetic enzymes in sympathetic ganglia. Finally, when chronically immobilized rats are exposed to novel stressors, levels of TH and PNMT in the adrenal medulla increase even further (Kvetnansky, 2004;Sabban & Serova, 2007;Sabban et al, 2006).…”
Section: Stressmentioning
confidence: 99%